2011
DOI: 10.1002/sia.3824
|View full text |Cite
|
Sign up to set email alerts
|

Engineered interface using a hydroxyl group‐free polymeric buffer layer onto a TiO2 nanocomposite film for improving the electrical properties in a low‐voltage operated organic transistor

Abstract: We demonstrate the effect of engineered interfaces by introducing different classes of polymeric buffer layers onto a titanium oxide (TiO 2 ) nanocomposite film on the density of interfacial trap sites and corresponding mobility in low-voltage-operated organic field-effect transistors. The organic field-effect transistors were fabricated using pentacene as an organic semiconductor layer and a high dielectric TiO 2 nanocomposite film for low-voltage operation stacked with two different kinds of thin polymers, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Under the guidelines of this concept, other hydroxyl-free polymers, such as polyethylene, poly(methyl methacrylate) and parylene, have been used as a buffer layer and n-type properties have been observed in most OFET cases, further confirming that high performance and stable n-type OFETs can be achieved through passivating the influence of the negative factors on electron transport. 40,41,98 For example, high performance n-type poly(benzobisimidazobenzophenanthroline) (BBL) polymer thin film transistors, with excellent device stabilities, have been achieved by Kim et al, 99 through modification of the dielectric/ semiconductor interfaces with a polymer buffer layer. The authors carried out a systematic study on the effect of the polymer dielectric constant on the n-type device performance and found that the electron mobility and device stability could be significantly increased by decreasing the dielectric constant of the polymer layers due to the reduced energetic expense of the charge-carrier/dipole interaction.…”
Section: Surfaces Chemically Modified By Samsmentioning
confidence: 99%
“…Under the guidelines of this concept, other hydroxyl-free polymers, such as polyethylene, poly(methyl methacrylate) and parylene, have been used as a buffer layer and n-type properties have been observed in most OFET cases, further confirming that high performance and stable n-type OFETs can be achieved through passivating the influence of the negative factors on electron transport. 40,41,98 For example, high performance n-type poly(benzobisimidazobenzophenanthroline) (BBL) polymer thin film transistors, with excellent device stabilities, have been achieved by Kim et al, 99 through modification of the dielectric/ semiconductor interfaces with a polymer buffer layer. The authors carried out a systematic study on the effect of the polymer dielectric constant on the n-type device performance and found that the electron mobility and device stability could be significantly increased by decreasing the dielectric constant of the polymer layers due to the reduced energetic expense of the charge-carrier/dipole interaction.…”
Section: Surfaces Chemically Modified By Samsmentioning
confidence: 99%
“…Such thin insulator layers result in very high leakage currents, especially in Ta 2 O 5 which has a comparatively small band gap (4.5 eV) when compared with other metal oxide dielectrics such as ZrO 2 , (7.8 eV) or Al 2 O 3 (8.9 eV). In addition, as in the case of other dielectric metal oxides, the surface hydroxyl (–OH) groups on the surface of tantalum oxide tend to create a large number of insulator/semiconductor interfacial traps which consequently imposes detrimental effects on TFT performance [17]. An effective method to passivate thin layers of metal oxide dielectrics in thin-film transistors is by making the surface considerably less polar via salinization.…”
Section: Introductionmentioning
confidence: 99%
“…The sub-threshold swing ( SS ) was calculated using the equation SS = dV GS / d (log 10 | I DS | ). The maximum and minimum values of I DS at a V DS of −20 V were designated as I ON (on current) and I OFF (off current), respectively [ 19 ]. The thickness-dependent properties of pentacene-based OTFTs with Teflon and F 4 TCNQ-doped pentacene interlayers of various thicknesses were summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%